(untitled) - Cascio, Wayne F. (Boston, 2010)
Links the relationship between productivity, quality of work life, and profits to various human resource management activities and as such, strengthens the students' perception of human resource management as an important function, which affects individuals, organizations, and society.
Keywords: Personnel management,Quản trị nhân sự